Sub-Saharan Africa - Improving Institutional and Economic Performance - World Bank (Washington, DC, 2012)
The institutional crisis affecting economic management in Sub-Saharan Africa (SSA) is a crisis of structural disconnect between formal institutions transplanted from outside and indigenous institutions born of the culture and traditional values of the African past. Building on the findings and recommendations of the new school of institutional economics, the study, Africa's management in the 1990s and beyond: Reconciling Indigenous and Transplanted Institutions (AM90s) posits that both formal and informal institutions are needed in Africa, but in a more flexible and adapted form. Formal institutions need to be adapted to the local culture/context, in order to build the legitimacy needed for enforceability. Informal institutions, although rooted in local culture, also need to adapt to the changing outside world and challenges. It is through this adaptation that formal and informal institutions can converge be reconciled and build on each other's strengths, transaction costs reduced and institutional performance maximized. This process for building convergence is at the heart of the institutional reconciliation paradigm proposed by the AM90s research program and calls for a truly participatory and synergistic approach. This institutional reconciliation is both possible and necessary to make civil services in SSA more service-oriented, develop the private sector, and improve the productivity of African enterprise.